If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (x + 4) + -3x = x + (x + 4) + 2(x + 4) Reorder the terms: x + (4 + x) + -3x = x + (x + 4) + 2(x + 4) Remove parenthesis around (4 + x) x + 4 + x + -3x = x + (x + 4) + 2(x + 4) Reorder the terms: 4 + x + x + -3x = x + (x + 4) + 2(x + 4) Combine like terms: x + x = 2x 4 + 2x + -3x = x + (x + 4) + 2(x + 4) Combine like terms: 2x + -3x = -1x 4 + -1x = x + (x + 4) + 2(x + 4) Reorder the terms: 4 + -1x = x + (4 + x) + 2(x + 4) Remove parenthesis around (4 + x) 4 + -1x = x + 4 + x + 2(x + 4) Reorder the terms: 4 + -1x = x + 4 + x + 2(4 + x) 4 + -1x = x + 4 + x + (4 * 2 + x * 2) 4 + -1x = x + 4 + x + (8 + 2x) Reorder the terms: 4 + -1x = 4 + 8 + x + x + 2x Combine like terms: 4 + 8 = 12 4 + -1x = 12 + x + x + 2x Combine like terms: x + x = 2x 4 + -1x = 12 + 2x + 2x Combine like terms: 2x + 2x = 4x 4 + -1x = 12 + 4x Solving 4 + -1x = 12 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 4 + -1x + -4x = 12 + 4x + -4x Combine like terms: -1x + -4x = -5x 4 + -5x = 12 + 4x + -4x Combine like terms: 4x + -4x = 0 4 + -5x = 12 + 0 4 + -5x = 12 Add '-4' to each side of the equation. 4 + -4 + -5x = 12 + -4 Combine like terms: 4 + -4 = 0 0 + -5x = 12 + -4 -5x = 12 + -4 Combine like terms: 12 + -4 = 8 -5x = 8 Divide each side by '-5'. x = -1.6 Simplifying x = -1.6
| (2x+8)-(7x^2+7x+4)= | | m+3+4=30 | | x=-7y | | 0=5x+2x^2-63 | | -3y+7=-4y+3 | | 14x^2-17xy+5y^2= | | 64-49y^2=0 | | 8x-4=6x-6 | | 10-6m=-104 | | 2x^2+7x-2=x^2+2x | | 4x^2-xy-3y^2= | | -10=10k-90 | | q+2=5 | | -103=-9x-13 | | x^2+8x+68=0 | | 9(9x+4)= | | x+(x+4)=2(x-3x) | | 10x^2-5x-5= | | 8-x+1=6 | | x+3x=2(x-4) | | 4y^2+20Y=0 | | 3(7x-5)= | | x+4=2(x-3x) | | p^2+5p=6 | | 2b^2=9b+5 | | 5(6+x)=85 | | x^2=4-7x | | 3(x^2-x)-4(x^2+x)=-3(x+1)-4(x+2) | | 3r^3+18r^2=21r | | 5x=32 | | 75y^2-147=0 | | 2x^2+9x=8 |